2022
DOI: 10.5751/es-13363-270327
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging emotion-behavior pathways to support environmental behavior change

Abstract: Many global environmental threats are driven by human behavior and require behavioral solutions. Researchers in the environmental field have recently explored the behavioral sciences as core to changing behavior for conservation, yet leveraging human emotions remains an underused tool for behavior change compared to others like social norms. Humans experience a range of emotions that each cause distinct patterns of behavior depending on unique contexts that evolved over time; this presents an opportunity to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…In increasingly globalized societies, the aspirational narratives of human development, including human rights and fair access to health, education and decent standards of living, have shaped decades of improvement in human wellbeing for billions of people [105,137]. Building on these narratives to include human rights to a 'clean and healthy environment' [138], together with narratives calling for rights of nature, multi-species justice and other hopeful aspirational narratives connecting human wellbeing with the wellbeing of the rest of nature are increasingly essential to shape a better planetary future [109,124,127,128,136,[139][140][141][142][143][144][145][146][147][148]. This is even more critical on a planet where people are increasingly connected with each other electronically, while living lives more physically distanced from daily contact with each other and the rest of life on Earth [106,149].…”
Section: (B) Anthropocene Opportunities: Human Aspirations Shape Plan...mentioning
confidence: 99%
See 1 more Smart Citation
“…In increasingly globalized societies, the aspirational narratives of human development, including human rights and fair access to health, education and decent standards of living, have shaped decades of improvement in human wellbeing for billions of people [105,137]. Building on these narratives to include human rights to a 'clean and healthy environment' [138], together with narratives calling for rights of nature, multi-species justice and other hopeful aspirational narratives connecting human wellbeing with the wellbeing of the rest of nature are increasingly essential to shape a better planetary future [109,124,127,128,136,[139][140][141][142][143][144][145][146][147][148]. This is even more critical on a planet where people are increasingly connected with each other electronically, while living lives more physically distanced from daily contact with each other and the rest of life on Earth [106,149].…”
Section: (B) Anthropocene Opportunities: Human Aspirations Shape Plan...mentioning
confidence: 99%
“…However, crisis narratives based on abstract and differentially experienced concerns, like the exceedance of a specific global temperature, tipping point or other planetary indicator, especially when attached to actions one cannot personally enact, impossible time limits (e.g. 'only 12 years to act') and government failures to act, can cause more anxiety than action [22,[124][125][126][127][128][129]. Even worse, crisis narratives, when developed and deployed primarily by elites, wellmeaning or otherwise, can drive divisions, disempowerment and conflict [125,[130][131][132].…”
Section: (B) Anthropocene Opportunities: Human Aspirations Shape Plan...mentioning
confidence: 99%
“…Several reviews of the role of emotions in climate action call for research to establish causal connections between emotions, contexts, and different environmental actions. Brosch (2021) and Williamson and Thulin (2022) point out that findings suggesting that people's affective responses to climate change are consistently among the strongest predictors of risk perceptions, personal protective behaviors, policy support, and technology acceptance, are all based on correlational data. The exploratory results presented above and discussed further in Constantino and Weber (2023) are suggestive but also correlational.…”
Section: Future Directionsmentioning
confidence: 99%
“…There is ample research showing that emotions are strongly linked to pro‐environmental behaviors, as shown by Brosch (2021) and Schneider et al (2021). Emotions are also often used as triggers to promote environmental behaviors (see Brosch, 2021; Williamson & Thulin, 2022). For a very long time, negative emotions, such as fear and guilt, have been considered a panacea in the environmental domain.…”
Section: Introductionmentioning
confidence: 99%
“…often used as triggers to promote environmental behaviors (see Brosch, 2021;Williamson & Thulin, 2022). For a very long time, negative emotions, such as fear and guilt, have been considered a panacea in the environmental domain.…”
mentioning
confidence: 99%